Pengaruh Sistem Informasi Sumber Daya Manusia, Kompetensi Dan Disiplin Kerja Terhadap Kinerja Aparat Desa Parumpanai - Kurniawan, Agung Widhi; Friska, Silvi; Ruma, Zainal; Sahabuddin, Romansyah; Burhanuddin (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of the human resource information system, competence and work discipline on the performance of the Parumpanai Villange officals.The type of research used is quantitative research,where this research is used to explain correlations and test the proposed hypotheses.The sample in this study used a saturated sample technique with a total of 16 respondents.Data collection techniques in this study used observation,questionnaires and documentation with multiple lienar regression analysis techniques.The results showed,that there is a positive and significant influence of human resource information systems,competence and work discipline as awhole on the performance o apparatus with apresentation of 44.7%.This implies that the dependent variable (employee performance) can be interpreted by human resource information systems,competence and work discipline of 44.7%, while 55.3% (100% 44.7%) is explained by causes and other factors that are outside the variables studied.